Associação entre a concentração sérica de ácido úrico e pressão arterial em crianças e adolescentes com excesso de peso - Carvalho, Natalia De [UNIFESP] (2019)
Objectives: To test the association between serum uric acid concentration and blood pressure in overweight children and adolescents. Methods: cross-sectional study with 187 children and adolescents between 8 and 12 years of age. We evaluated weight, height, waist circumference, Tanner pubertal stage, blood pressure and serum uric acid concentration. To test the association of serum uric acid concentration (UA) with blood pressure (BP), univariate linear regression was performed, in which BP was the outcome variable. In addition to AU, the following covariates were considered: a) sex, b) age, c) BMI Z-score, and d) waist circumference and interaction between UA and each other covariate. Finally, we performed the multivariable linear regression analysis. Results: We found no association between serum uric acid concentration and systolic blood pressure (p=0.410) and diastolic blood pressure (p=0.806). When we evaluated the interaction of uric acid with other independent variables, we found a positive effect of the interaction between serum uric acid concentration and age on both systolic blood pressure (p=0.001) and diastolic blood pressure (p=0.024). However, this association did not remain positive after analysis of multivariate linear regression. Conclusion: we conclude that serum uric acid concentration has no effect on blood pressure in the sample of children and adolescents studied. However, our data suggest that this association might happen in older children.